Insertion of large diameter through-thickness metallic pins in composites. (April 2022) - Neale, Geoffrey; Skordos, Alex
Graphical abstract: Highlights: New method for insertion of large diameter pins in prepreg composite laminates. Conical leading-edge pins exhibit low insertion force with better insertion quality. Insertion forces increase exponentially with pin diameter. Prepreg stack consolidation improves insertion quality by reducing tow distortions. Abstract: Existing Through-Thickness Reinforcement (TTR) methods for laminated composites using semi or fully rigid reinforcing elements, like tufting, stitching, and z-pinning, present limitations on reinforcing element geometry, strength, and stiffness. Where these application envelopes are exceeded, TTR element insertion results in unacceptable levels of damage to both the composite and/or TTR elements. Here, we demonstrate that low-speed insertion of rigid reinforcements into heated prepreg preforms is a feasible and robust reinforcement process capable of providing accurate TTR element placement with minimal tow disturbance compared with existing methods for similar pin sizes. The insertion process is characterised with respect to insertion forces, and mesoscale laminate deformation/damage for carbon-benzoxazine prepreg preforms. The research investigates the influence of pin leading edge on insertion for a range of pin diameters (1.2, 1.5, and 2.0 mm) and preform consolidation states, describing low insertion forces and good quality laminate preforms. Insertion forces increase with pin diameter, typically resulting from increased pin-tow contact area and friction. Large diameter sizes and low insertion forces expand the range and forms of materials that can be inserted compared to existing TTR methods and show that this method can potentially be transferred to benefit work on composite hole creation, joining, and repair.